Kebijakan Kontroversial Pemerintah Orde Baru di Ranah Pendidikan Tinggi Indonesia dalam Perspektif Historis - Kurniawan, Dadan Adi; Wijaya Putri, Alifah Diah; Pratama, Yuandhi Yuan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study examines several controversial policies of the New Order government as a manifestation of educational politics in the realm of higher education. This study uses a historical method consisting of five steps by Kuntowijoyo, namely topic determination, heuristics, criticism, interpretation, and historiography. The data collection technique uses historical literature studies by utilizing various sources such as journals, books, theses, and articles that are credible and relevant. The results of the study show that several controversial policies of the New Order in the realm of higher education are the implementation of NKK/BKK to sterilize campuses from political activities that have the potential to endanger the stability of security and government power. More specifically, the government prohibits and complicates licensing for student activities to hold demonstrations, seminars, discussions, and other activities aimed at criticizing the government. In addition, lecturers and students are also prohibited from using left-wing learning resources that are contrary to Pancasila. Other controversial policies include the centralized election of campus leaders, the prohibition of long hair and the prohibition of wearing the hijab. Higher education level becomes one of the strategic spaces that cannot escape from the tight supervision, control, political and ideological interests of the rulers. As a result, the campus democracy is increasingly dimming due to the limited space for movement and expression of students, especially in non-academic matters.